Arten der Hygrogeus-Gruppe aus dem Fernen Osten Russlands, aus Japan und China (Coleoptera, Staphylinidae, Omaliinae, Anthophagini) (Beiträge zur Kenntnis ostpaläarktischer Insekten; 13). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Geodromicus abdominalis sp. n. from the Far East of Russia (Primorskiy Kray) is described and compared with Geodromicus caliginosus (Sharp, 1889) and Geodromicus beibienkoi Tichomirova, 1973. Geodromicus kirschenblati Tichomirova, 1973 is resurrected from the synonymy with Geodromicus sibiricus Bernhauer, 1915. The following two synonyms are established: Geodromicus kirschenblati Tichomirova, 1973 = Psephidonus iburinus Watanabe, 1990 syn. n. and Geodromicus sibiricus Bernhauer, 1915 = Psephidonus nipponensis Watanabe, 1990 syn. n. For Geodromicus sibiricus Bernhauer, 1915 the type locality is specified. It is in the Chinese province Heilongjiang, not in the Russian East-Sibiria. For nine species new records are listed. Geodromicus lestevoides (Sharp, 1889) and Liophilydrodes puncticollis (Nakane & Sawada, 1956) are new for Russia. A key is given for the six species of the genera Geodromicus and Liophilydrodes from the Russian Far East.KeywordsColeoptera, Staphylinidae, Omaliinae, Geodromicus, Liophilydrodes, Philydrodes, new species, revalidation, new synonyms, key, Russian Far East, Japan, China.Nomenclatural Actsabdominalis Zerche, 2003 (Geodromicus), spec. n.iburinus Watanabe, 1990 (Psephidonus), syn. n. of Geodromicus kirschenblati Tichomirova, 1973nipponensis Watanabe, 1990 (Psephidonus), syn. n. of Geodromicus sibiricus Bernhauer, 1915